The fragile X chromosome (GCC) repeat folds into a DNA tetraplex at neutral pH - Fojtík, P; Vorlícková, M (Nucleic acids research, 2001)
UV absorption and CD spectroscopy, along with polyacrylamide gel electrophoresis, were used to study conformational properties of DNA fragments containing the trinucleotide repeat (GCC)(n) (n = 4, 8 or 16), whose expansion is correlated with the fragile X chromosome syndrome. We have found that the conformational spectrum of the (GCC)(n) strand is wider than has been shown so far. (GCC)(n) strands adopt the hairpin described in the literature under a wide range of salt concentrations, but only at alkaline (>7.5) pH values. However, at neutral and slightly acid pH (GCC)(4) and (GCC)(8) strands homodimerize. Our data suggest that the homodimer is a bimolecular tetraplex formed by two parallel-oriented hairpins held together by hemi-protonated intermolecular C.C(+) pairs. The (GCC)(16) strand forms the same tetraplex intramolecularly. We further show that below pH 5 (GCC)(n) strands generate intercalated cytosine tetraplexes, whose molecularity depends on DNA strand length. They are tetramolecular with (GCC)(4), bimolecular with (GCC)(8) and monomolecular with (GCC)(16). i-Tetraplex formation is a complex and slow process. The neutral tetraplex, on the other hand, arises with fast kinetics under physiological conditions. Thus it is a conformational alternative of the (GCC)(n) strand duplex with a complementary (GGC)(n) strand.
Keywords: syndrom fragilního X; DNA; Trinucleotide Repeats; Spectrophotometry, Ultraviolet; konformace nukleové kyseliny; Dimerization; Humans; Electrophoresis, Polyacrylamide Gel; Nucleic Acid Conformation; lidé; trinukleotidové repetice; dimerizace; Fragile X Syndrome; elektroforéza v polyakrylamidovém gelu; spektrofotometrie ultrafialová; cirkulární dichroismus; Circular Dichroism